Estimated HIV Trends and Program Effects in Botswana - Stover, John (Public Library of Science, 2008)
BACKGROUND: This study uses surveillance, survey and program data to estimate past trends and current levels of HIV in Botswana and the effects of treatment and prevention programs. METHODS/PRINCIPAL FINDINGS: Data from sentinel surveillance at antenatal clinics and a national population survey were used to estimate the trend of adult HIV prevalence from 1980 to 2007. Using the prevalence trend we estimated the number of new adult infections, the transmission from mothers to children, the need for treatment and the effects of antiretroviral therapy (ART) and adult and child deaths. Prevalence has declined slowly in urban areas since 2000 and has remained stable in rural areas. National prevalence is estimated at 26% (25–27%) in 2007. About 330,000 (318,000–335,000) people are infected with HIV including 20,000 children. The number of new adult infections has been stable for several years at about 20,000 annually (12,000–26,000). The number of new child infections has declined from 4600 in 1999 to about 890 (810–980) today due to nearly complete coverage of an effective program to prevent mother-to-child transmission (PMTCT). The annual number of adult deaths has declined from a peak of over 15,500 in 2003 to under 7400 (5000–11,000) today due to coverage of ART that reaches over 80% in need. The need for ART will increase by 60% by 2016. CONCLUSIONS: Botswana's PMTCT and treatment programs have achieved significant results in preventing new child infections and deaths among adults and children. The number of new adult infections continues at a high level. More effective prevention efforts are urgently needed.